Cationic polymerization of isobutylene at room temperature - Kostjuk, Sergei V.; Yeong, Hui Yee; Voit, Brigitte (Journal of Polymer Science Part A-Polymer Chemistry, 2013)
This review highlights recent approaches toward polyisobutylene (PIB) by an energy efficient room temperature cationic polymerization. Special focus is laid on our own work using modified Lewis acids and nitrile-ligated metal complexes associated with weakly coordinating anions. In both cases, suitable conditions have been found for efficient production of PIB characterized by medium to low molar masses and a high content of exo double bonds as end groups - the typical features of highly reactive PIB, an important commercial intermediate toward oil and gasoline additives. These and other approaches demonstrate that the cationic polymerization of isobutylene is still not fully explored, and new innovative catalyst systems can lead to surprising results of high commercial interest. © 2012 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-03-20
Keywords: catalysis; cationic polymerization; polyisobutylene; polyolefins; room temperature; weakly coordinating anions